2019
DOI: 10.3847/1538-4357/ab2da3
|View full text |Cite
|
Sign up to set email alerts
|

Investigating “Dark” Energy in the Solar Corona Using Forward Modeling of MHD Waves

Abstract: It is now well established that the Alfvénic waves are ubiquitous in the solar corona. However, the Alfvénic wave energy estimated from the Doppler velocity measurements in the corona was found to be four orders of magnitude less than that estimated from non-thermal line widths. McIntosh & De Pontieu (2012) suggested that this discrepancy in energy might be due to the line-of-sight (LOS) superposition of the several oscillating structures, which can lead to an underestimation of the Alfvénic wave amplitudes an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 68 publications
0
63
0
Order By: Relevance
“…Previous studies have demonstrated that the damping of kink oscillations by resonant absorption is also not sensitive to loops being multi-stranded (Terradas et al, 2008b;Pascoe et al, 2011). However, the presence of such structuring is of interest since it can lead to a significant underestimation of the wave energy estimated using Doppler measurements (De Moortel and Pascoe, 2012;Pant et al, 2019) or an overestimation of the broadness of DEM spectra (Van Doorsselaere et al, 2018). Due to LOS integration of optically thin EUV emission it is difficult to interpret fine structure in transverse intensity profiles, particularly when using a single channel as may be the case for coronal loops which are often identifiable only in the 171 Å channel of SDO/AIA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that the damping of kink oscillations by resonant absorption is also not sensitive to loops being multi-stranded (Terradas et al, 2008b;Pascoe et al, 2011). However, the presence of such structuring is of interest since it can lead to a significant underestimation of the wave energy estimated using Doppler measurements (De Moortel and Pascoe, 2012;Pant et al, 2019) or an overestimation of the broadness of DEM spectra (Van Doorsselaere et al, 2018). Due to LOS integration of optically thin EUV emission it is difficult to interpret fine structure in transverse intensity profiles, particularly when using a single channel as may be the case for coronal loops which are often identifiable only in the 171 Å channel of SDO/AIA.…”
Section: Discussionmentioning
confidence: 99%
“…A transfer of wave energy from collective kink motions to localized azimuthal perturbations (m = 1 Alfvén waves) will appear as a damping of the periodic loop displacement. The azimuthal motions will typically appear as unresolved Doppler velocity perturbations due to line-of-sight (LOS) integration of multiple waves and structures (e.g., De Moortel and Pascoe, 2012;Pant et al, 2019). Although this transfer is a linear and ideal process, subsequent phase-mixing of the Alfvén waves in the inhomogeneous layer can generate small spatial scales which enhance dissipative processes such as viscosity and resistivity (e.g., Pagano and De Moortel, 2017;Pagano et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In practice, estimates of the total kinetic energy are likely to be between these two cases and could underestimate the true kinetic energy by an order of magnitude, where some of this energy will be represented by enhanced non-thermal line widths (e.g. McIntosh & De Pontieu 2012;Pant et al 2019). Of course, additional uncertainties in the density profile and the LOS integration length may further increase the uncertainty in the energy measurements.…”
Section: Discussionmentioning
confidence: 99%
“…McIntosh & De Pontieu 2012). Similarly, Pant et al (2019) investigate the discrepancy between the observed wave energy, calculated from the Doppler velocities, and the true wave energy and find that the additional energy is present in the non-thermal line widths. Figure 22 shows the evolution of the average line width, calculated using the full-width-half-maximum (FWHM) of the Fig.…”
Section: Los Kinetic Energymentioning
confidence: 99%
“…More quantitative predictions of the line profiles have recently been developed based on waves injected into the loophowever, they fail to simultaneously reproduce both observed temperatures and non-thermal broadening. On the one hand, 3D MHD models that excite transverse MHD waves through velocity drivers with prescribed amplitudes find that the line-ofsight superposition of large-amplitude Alfvénic waves in the coronal loops could result in a large non-thermal broadening of the spectral lines (Pant et al 2019). However, those models do not simultaneously heat the plasma with those waves to the required temperatures.…”
Section: Previous Hypotheses and Modellingmentioning
confidence: 99%